THE COMPETITIVENESS OF LABUAN BAJO WITH SENTIMENT ANALYSIS - Adicatra, Dayu Cakasana; Dias Satria (Contemporary Studies in Economic, Finance and Banking, 2024)
TripAdvisor is one of the popular websites that collects various traveler reviews of tourism place that have been visited by its users. Reviews are important factors that influence the decision or motivation of a tourist to go to a tourism place. Labuan Bajo is one of the tourism sites that have been given a lot of reviews on TripAdvisor. Looking at this aspect, this study utilized the reviews of foreign tourists to increase competitiveness and economic activity atLabuan Bajo. Research data were obtained directly from the internet using data mining methods for later analysis. This study employed sentiment analysis method. The results of sentiment analysis in this study are information and suggestions for improving the competitiveness and economic activities of Labuan Bajo to be better.